PAHs in toasted bread: determination using microwave-assisted extraction and dispersive liquid–liquid microextraction followed by high-performance liquid chromatography. Issue 20 (14th May 2018) - Mahmoudpour, Mansour; Pilevar, Zahra; Javanmardi, Fardin; Taram, Faran; Mousavi, Mir-Michael
Abstract : In the present study, a fast, simple, and efficient method for the determination of PAHs in toasted bread was developed using microwave-assisted extraction (MAE) and dispersive liquid–liquid microextraction (DLLME) followed by high-performance liquid chromatography (HPLC). Abstract : In the present study, a fast, simple, and efficient method for the determination of PAHs in toasted bread was developed using microwave-assisted extraction (MAE) and dispersive liquid–liquid microextraction (DLLME) followed by high-performance liquid chromatography (HPLC). Parameters, such as the nature of alkaline aqueous solution, extraction and disperser solvents, microwave time, and pH, affecting MAE-DLLME performance were studied and optimized. MAE-DLLME method followed by HPLC could provide excellent enrichment factors in the range of 255–312 for PAHs. Intra- ( n = 6) and inter-day ( n = 5) precisions of the method were satisfactory, with relative standard deviations less than or equal to 5.78 (10 ng g −1 of each analyte). Calibration curves were linear for concentrations in the range from 0.1 to 15 ng g −1 and with correlation coefficients ranging from 0.997 to 0.999. Limits of detection (LODs) based on the signal-to-noise ratio (S/N) of 3 are 0.03, 0.34, 0.27, and 0.19 ng g −1 for benzo[ a ]anthracene, benzo[ b ]fluoranthene, benzo[ a ]pyrene, and chrysene, respectively. The recoveries of these compounds were from 87 to 104%. A comparison of the proposed method with the existing methods reported in the literature demonstrates that the proposed method is simple with low extraction time, cost efficient, highly selective, and sensitive; moreover, it provides good enrichment factors to determine PAHs in toasted bread.